Plan de mejoramiento para la empresa Rincon Aguilar Consultores (2013)
This paper is the result of a research seeking to holistically analyze “RINCON AGUILAR CONSULTORES S.A.C” consulting company, and propose an enhancement plan based upon findings. This will permit the company to generate bigger economic dynamics, improving competitiveness and productiveness. MMGO matrix was used as a meticulous diagnostic tool where the activities that will make part of the change, the enhancement, and the modernization in the organization will be identified. Likewise, it systematically establishes the priorities for the modernization projects, and proposes descriptors for the activities and elements which the company must possess, defining the routes that allow the optimization of said key elements. This is made up of 15 components that involve all areas of the company both internally and externally. In addition, the 5 Porter forces model was used; Industrial Matrix, IFAS, EFAS charts, and SWOT matrix. Based on this, a changing route is a proposed with is strategies and action plan. While this is focused on developing an enhancement proposal, it is intended to contribute to the compilation of information and expertise in consulting companies in Colombia where there is not a significant record of information or knowledge that allows a reference to those researchers in the area so as to create, develop, and promote the culture with regard to this activity. It began with a specific case and context, the consulting company, “Rincon Aguilar Consultores S.A.C” It can be useful to generalize situations, key analytical factors, and understanding of the dynamics of a complexity of a consulting and formation business.